Identifikasi molekuler lepidopteran predator Coccidae pada tanaman kopi di Sukabumi: Molecular identification of predatory Lepidoptera of Coccidae on coffee plants in Sukabumi - Arlia Dwi Hapsari; Santoso, Sugeng; Kusumah, R. Yayi Munara (Jurnal Entomologi Indonesia, 2024)
A predatory Lepidoptera that has the potential to be a biological control agents of the soft scale insect (Coccidae) on coffee plants (Coffea spp.) was found in Sukabumi, West Java. However, information regarding the species name of predatory Lepidoptera has never been reported in Indonesia. Literature for morphological identification of this predatory Lepidoptera species is limited. Therefore, this study was conducted to identify predator species molecularly. Predators were collected from coffee plantations that were infested by soft scale in Sukabumi, West Java. Identification using the PCR procedures of mitochondrial COI gene was carried out in the laboratory. The results show that the sample DNA sequences (629 bp) has a similarity level of 95.67% (GenBank) and 95.37% (BOLD Systems) to the Autoba rubra Hampson species. Based on phylogeny analysis, the sample is also closely related to Mataeomera spp. The DNA sequences alignment variation of sample and four species voucher A. rubra in the GenBank database was 7.58%. Therefore, it can be concluded that the predatory Lepidoptera preying on soft scale insects on coffee plants in Sukabumi are most closely related to A. rubra.